Midpoint potential compensation balance control method based on virtual space vector pulse‐width modulation for NPC three‐level inverter. (24th June 2019) - Fan, Bo; Fu, Zhumu; Fu, Jiangtao; Liu, Leipo
Abstract : The neural‐point‐clamped (NPC) three‐level inverters exhibit a midpoint potential unbalance problem. With the analysis on the midpoint potential fluctuation, its voltage vectors are discussed, and the mathematical model of the midpoint current in each sector is established. Based on virtual space vector pulse‐width modulation (VSPWM) calculated in the gh coordinate, a balance control method is proposed to compensate the midpoint potential. The virtual medium vector and voltage adjustment factor are introduced. Different positive and negative short vectors are distributed to different adjustable parameters to improve the influence of short vectors on the midpoint potential. The experimental results show that the proposed method balances the midpoint potential effectively, and VSVPWM with the gh coordinate can reduce the complexity of the calculation.